Organization of Distance Education in the System of Teacher Postgraduate Education - KASHYNA, GANNA; NIKOLAIEV, KYRYLO (Journal of Education, Technology and Computer Science, 2016)
The process of development, theoretical substantiation and implementation of distance education system organization model into teacher postgraduate education has been considered in the paper. Postgraduate pedagogical study with wide-area distance study is greatly distinguished from present system by level of study quality, number of users, focus on personality, democracy, variance, application of modern information-communication technologies and telecommunication networks in study. The platform of distance education has to be applied for supplement and expansion of traditional process of institution study and communication in the teacher postgraduate education institutes. Implementation of distance education in the teacher postgraduate education system creates the educational system of retraining and professional development for teachers onthe- job, and improvement of educational services, proposed by educational institution.